Ontology of Teamwork Competency and Approaches to Its Development at Engineering University - M. N. Filatova; V. S. Sheinbaum; P. G. Shchedrovitsky (Moscow Polytechnic University, 2018)
The article addresses the question of the professional component in "teamwork skills", which the authors consider to be of paramount importance when it comes to engineering activities. In this regard, the requirements of the professional standards for engineering activities and Federal State Educational Standards are compared. The gaps in the positions of employers and the academic community regarding this competency is recorded. From the general methodological and praxeological positions, the ontology of "teamwork" competency is considered in the article and the need to orient engineering universities to develop students' teamwork skills as a professional competence is argued. The authors adduce the results of the 10-year experience of Gubkin Russian University of Oil and Gas in implementation of interdisciplinary trainings in a virtual environment of professional activity. During the trainings sessions the students acquire the necessary teamwork skills such as: 1) systemic vision of engineering activities in oil and gas complex, understanding of its goals, specificity, multidimensional nature, conflict of interests, principles of division of labor, 2) communication skills for interaction in interdisciplinary team , 3) the experience of joint analysis of problem situations and their solutions in conditions of limited information, uncertainty, conflict of participants' interests, 4) assessment of project and managerial decisions. The proposed approach is based on the methodology of Organizational and Activity Games created by G.P. Shchedrovitsky in 1970s and developed by the Moscow Methodological Circle. This methodology is being applied for solving problem situations by teams in various areas of practices in conditions of limited information.